Colonisation of lettuce by Listeria monocytogenes and its biofilm formation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Microbiology at Massey University, Manawatu, New Zealand - Kyere, Emmanuel Owusu (Massey University, 2020)
Foodborne outbreaks associated with fresh produce due to pathogenic bacteria such as 𝘓𝘪𝘴𝘵𝘦𝘳𝘪𝘢 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴 (𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴) are increasing. A survey conducted as part of this study showed 5% of bagged lettuces sold at retail outlets contained 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴. The ability of 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴 to form biofilms is a concern in terms of fresh produce safety. The use of hydroponics (growing plants in nutrient solution without using soil) in fresh produce production is a more controlled environment than soil, and therefore may be easier to prevent pathogen contamination. The aim of this study was to determine whether hydroponic grown lettuce and UV-C stress can reduce the colonization, growth and biofilm formation of three fresh produce related strains of 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴: PFR O8A06 (coleslaw isolate), PFR O8A07 and PFR O8A08 (cabbage isolates) on lettuce. Evaluation of the nutrient content and indigenous microbiota between hydroponic and soil grown lettuces revealed significant differences. 16S rRNA amplicon sequencing of the bacterial community associated with hydroponically grown lettuce showed that it was more diverse than soil-grown lettuce. 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 was found to be the dominant bacteria on hydroponically grown lettuce while 𝘉𝘢𝘤𝘪𝘭𝘭𝘶𝘴 was found to be dominant in soil grown lettuce. There was no significant difference (p > 0.05) in 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴 attachment to both hydroponic and soil grown lettuce leaves under minimal exposure times. Exposure of lettuce to 5 log CFU/ml for just one second resulted in at least 0.77 log CFU/cm² attachment. 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴 was able to survive and grow on both lettuce leaf surfaces at 4 and 10°C. Both hydroponic and soil grown lettuce leaf extracts enhanced the survival, growth and biofilm formation of 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴s on stainless steel coupons, representing surfaces in lettuce processing plants. The results of this study demonstrate the ability of 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴 to colonize and form biofilms on lettuce irrespective of the growth system used. Finally, UV-C (1.3 kJm⁻²) on lettuce produced a stress response in the plants that reduced 𝘓. 𝘮𝘰𝘯𝘰𝘤𝘺𝘵𝘰𝘨𝘦𝘯𝘦𝘴 attachment, survival and growth at pre-harvest. Further exploration of this technique may enhance the microbial safety of lettuce.
Keywords: Lettuce; Microbiology; Listeria monocytogenes; Biofilms; 310799 Microbiology not elsewhere classified